Characteristics of Indonesian Consumers and Online Purchasing Behavior - Andini, Monika Dwi (Perhimpunan Sarjana Ekonomi dan Bisnis, 2023)
The growth of the online market in Indonesia is in the fast category, especially since the pandemic occurred in early 2020. In fact, there has been a shift in the way of buying in Indonesian society, especially among urban communities. Apart from these circumstances, the actual increase in online purchases is inseparable from the characteristics of the consumers themselves. That the pandemic is a trigger that strengthens the characteristics of Indonesian consumers to switch to a digital lifestyle. Based on this explanation, the motive of this study is to reveal the characteristics of the Indonesian market for the shift in consumption style, from conventional to digital. Therefore, quantitative research methods are used as an effort to scientific disclosure. The subjects of this research are urban communities in Indonesia who are used to making online purchases in various marketplaces and social media, such as Tiktok and Instagram. The number of respondents in this study were 300 people using a simple random sample technique. The results of the study explain that changes in buying behavior from conventional to online are caused by internal factors of the consumers themselves, for example the strong desire to buy online which is considered easy and economical. Then, there are indications of hedonic behavior spoiled by profitable online purchasing systems, such as free shipping and lower prices.